The transitivity function as an approach a character analysis of "Magnificence" - Tanchico, Maria Theresa Trinidad R.
This thesis presents a study of the characters of Estrella Alfon's short story entitled "Magnificence" using the transitivity function as an approach. The linguistic reading of the literary piece enhanced the interpretation of the text. It led to a fuller understanding of how language greatly signifies the trait and the role of a character in the story. The use of transitivity function showed how the verbs or processes as well as the role taken by the characters bring relevant and objective interpretations that are vital to the character analysis. On the whole, the transitivity function is a valuable approach to character analysis as it successfully describes the personalities that delineate the characters of "Magnificence".